[Letter from Abū Saʿīd b. Abū l-Ḥasan al-Abzārī] - Abzārī, Abū Saʿīd b. Abū l-Ḥasan al-
Letter from Abū Saʿīd b. Abū l-Ḥasan al-Abzārī, somewhere in the Maghrib, to his brother Abū l-Barakāt, in Fustat. In Judaeo-Arabic. Dated: Last decade of Nisan 1448 Seleucid = mid-April 1137 CE. (Gil dated it to ca. 1098 CE before the join was identified.) The sender traveled from Fustat for trading and arrived in Bijāya as intended. The Christian ship he traveled with encountered a Muslim fleet that captured Jerba. He describes the naval battle in the Mediterranean between Christians and Muslims, in addition to dealing with other mercantile affairs. Join: Oded Zinger. (Information in part from Gil, Kingdom, Vol. 4, #831.) VMR.
Keywords: Judaïsme – Djerba